Padronização e detalhamento de ligações metálicas - Mastela, Leonor da Cunha (2004)
The development of steel construction requires the advance of analysis, design, and construction techniques. Steel elements are joined by means of connections and designers do not always give them the attention they deserve. Connections might have not only sufficient strength but also adequate flexibility, which must correspond to the structural model hypotheses. The purpose of this work is to collate and organize tools for a rational design of steel connections. Design rules and practical recommendations are investigated. Connection components are individually studied in order to establish a general verification method. Welding properties, welding processes and bolted connections are presented. Inspection procedures and quality control practices are described. The verification of welds,bolts and their surrounding areas is based on a general mathematical procedure. Connections are categorized according to their stiffness and loading and different connection types are analysed in detail. Structural models, construction aspects and verification procedures are discussed.